Impact of human schistosomiasis in sub-Saharan Africa - Adenowo,Abiola Fatimah (2015)
Schistosomiasis, a neglected tropical disease of poverty ranks second among the most widespread parasitic disease in various nations in sub-Saharan Africa. Neglected tropical diseases are causes of about 534,000 deaths annually in sub-Saharan Africa and an estimated 57 million disability-adjusted life-years are lost annually due to the neglected tropical diseases. The neglected tropical diseases exert great health, social and ﬁnancial burden on economies of households and governments. Schistosomiasis has profound negative effects on child development, outcome of pregnancy, and agricultural productivity, thus a key reason why the "bottom 500 million" inhabitants of sub-Saharan Africa continue to live in poverty. In 2008, 17.5 million people were treated globally for schistosomiasis, 11.7 million of those treated were from sub-Saharan Africa. This enervating disease has been successfully eradicated in Japan, as well as in Tunisia. Morocco and some Caribbean Island countries have made signiﬁcant progress on control and management of this disease. Brazil, China and Egypt are taking steps towards elimination of the disease, while most sub-Saharan countries are still groaning under the burden of the disease. Various factors are responsible for the continuous and persistent transmission of schistosomiasis in sub-Saharan Africa. These include climatic changes and global warming, proximity to water bodies, irrigation and dam construction as well as socio-economic factors such as occupational activities and poverty. The morbidity and mortality caused by this disease cannot be overemphasized. This review is an exposition of human schistosomiasis as it affects the inhabitants of various communities in sub-Sahara African countries. It is hoped this will bring a re-awakening towards efforts to combat this impoverishing disease in terms of vaccines development, alternative drug design, as well as new point-of-care diagnostics.